Have acid base practicum at school in Muara Enim district oriented to environmental literacy? - N D Naomi; M Arifin; H Sholihin (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aimed to obtain information about practicum activities of acid-base which have been done in schools. This study was a qualitative method involving analysis of 5 lesson plan and its instruments. The results of this study were: First, student learning activity on acidbase material less integrated to environmental phenomenon. Second, teachers lesson plan did not relate between concepts and application concept, especially on the environment. Third, practicum only lifted concept and did not have orientation to environmental literacy. Forth, lack of practicum skills' assessment. The findings indicated that there was a learning innovation need through development of a practicum about environmental issue to build environmental literacy of students.